2019
DOI: 10.31788/rjc.2019.1235220
|View full text |Cite
|
Sign up to set email alerts
|

ADSORPTION OF M(II) (M = Mn, Cu, Zn) IN VARIOUS pH AND CONTACT TIME USING CHITOSAN-SILICA PREPARED BY SOL-GEL METHOD

Abstract: Chitosan-silica prepared by sol-gel method was used for adsorption of M(II) (M = Mn 2+ , Cu 2+ , Zn 2+ ) in solution at room temperature. The prepared chitosan-silica was characterized by Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). Effect of pH of the metal solution and adsorption contact time toward the adsorption capacity were investigated. The correlation between M(II) concentrations and the adsorption capacity, which was determined at optimum pH and optimum adsorption contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…At the current study, it was found that the silica sol could be extracted from this silicate metal solution via sol gel method. 10,12 Silica acts as a source for a large number of silica-based products supporting chemical, 13 and other manufacturing industries. 14 Previous study reported utilization of silica with large specific surface area and array ordered hexagonal, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…At the current study, it was found that the silica sol could be extracted from this silicate metal solution via sol gel method. 10,12 Silica acts as a source for a large number of silica-based products supporting chemical, 13 and other manufacturing industries. 14 Previous study reported utilization of silica with large specific surface area and array ordered hexagonal, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to obtain silica as a heavy metal adsorbent with reasonable efficiencies, such as absorbing heavy metals from wastewater, resulting in an iron reduction by more than 0.1 ppm [7]. Silica also has been widely used as an adsorbent to reduce several pollutants in water and wastewater treatment, such as Pb 2+ [8], Mn 2+ [9], Cd [10]. SG should be modified.…”
mentioning
confidence: 99%